The Antioxidant activity of plant secondary metabolites - Marčetić, Mirjana; Arsenijević, Jelena (Archives of Pharmacy, 2023)
Oxidative stress can induce the development of many different disorders. Plant secondary metabolites may act as antioxidants by neutralisation of free radicals and by stimulation of endogenous antioxidant mechanisms. One of the important secondary plant metabolites with antioxidant activity are polyphenols. They can exert activity by different mechanisms depending on their structure. Polyphenols are widely distributed in herbal drugs and some of commonly used are aronia berry (Aroniae fructus) and bilberry fruits (Myrtilli fructus), both rich in anthocyanins and tannins and with high antioxidant activity. Main compounds in turmeric rhizome (Curcumae rhizome) are curcuminoides that manifest antioxidant and anti-inflammatory activity. Furthermore, tea leaf (Camelliae sinensis folium) and coffee bean (Coffeae semen), highly present in every-day life, significantly contribute to daily intake of antioxidants and provide necessary protection of the organism from the consequences of oxidative stress.